2008
DOI: 10.1099/ijs.0.65370-0
|View full text |Cite
|
Sign up to set email alerts
|

Gene sequences of the pil operon reveal relationships between symbiotic strains of Vibrio fischeri

Abstract: Symbiosis between the bobtail squid Euprymna scolopes (Mollusca: Cephalopoda) and Vibrio fischeri bacteria has been a well-studied model for understanding the molecular mechanisms of colonization and adherence to host cells. For example, pilin expression has been observed to cause subtle variation in colonization for a number of Gram-negative bacteria with eukaryotic hosts. To investigate variation amongst pil genes of closely related strains of vibrios, we amplified pil genes A, B, C and D to determine orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Interestingly, V. cholerae colonization factors (e.g., genes responsible for pili formation) primarily reside on Chromosome I. Consequently, different V. fischeri ecotypes could be the result of evolution at loci involved in metabolism as opposed to those involved in tissue colonization ( Browne-Silva and Nishiguchi, 2007 ; Soto et al, 2014 ). Experimental evolution studies with E. coli have demonstrated that resource partitioning and alternative substrate specialization is sufficient for ecological polymorphisms to arise in prokaryotes ( Rosenzweig et al, 1994 ).…”
Section: Two-chromosome Genomic Architecture In Vibrionaceae Evolvabmentioning
confidence: 99%
“…Interestingly, V. cholerae colonization factors (e.g., genes responsible for pili formation) primarily reside on Chromosome I. Consequently, different V. fischeri ecotypes could be the result of evolution at loci involved in metabolism as opposed to those involved in tissue colonization ( Browne-Silva and Nishiguchi, 2007 ; Soto et al, 2014 ). Experimental evolution studies with E. coli have demonstrated that resource partitioning and alternative substrate specialization is sufficient for ecological polymorphisms to arise in prokaryotes ( Rosenzweig et al, 1994 ).…”
Section: Two-chromosome Genomic Architecture In Vibrionaceae Evolvabmentioning
confidence: 99%
“…The clearly separated rumoiensis clade consists of Vibrio rumoiensis (Yumoto et al, 1999) and Vibrio litoralis (Nam et al, 2007) and forms a distant lineage within the genus. Micro-organisms belonging to the genus Vibrio are known to live either freely or associated as symbionts with aquatic animals in marine or estuarine waters (Browne-Silva & Nishiguchi, 2008) or as parasites of fish, crustaceans and molluscs (Thompson et al, 2004). Vibrio species have been reported less frequently as members of microbial consortia on cheese surfaces (Feurer et al, 2004), but some studies have suggested that they play a role in the ripening process (ElBaradei et al, 2007).…”
mentioning
confidence: 99%
“…In V. fischeri , pilus subunits are synthesized by the pilABCD operon, where pilA contributes to colonization effectiveness and encodes a protein similar to type IV-A pilins (where mshA is a close relative [25], [26]. Phylogenetic and molecular differences have also been observed in pilB and pilD loci among multiple V. fischeri strains isolated from different squid hosts [27]. Our study demonstrates that V. fischeri ETJB1C pilC complemented with non-native Hawaiian V. fischeri ES114 pilC (- pilC ETJB1H:: pilC ES114) is dominant in E. scolopes , but loses in E. tasmanica , since there is a competitive dominance for the native pilC locus (Fig.…”
Section: Resultsmentioning
confidence: 99%